Graph Coloring Implementation Using Welch Powell Algorithm In Lecture Scheduling Design For Mathmatics Department - Cipta, Hendra; Widyasari, Rina; Batubara, Fikri Husin (Universitas Wiralodra, 2023)
Designing the scheduling of lecture rosters is one of the common problems faced by all universities. The problem that often occurs as a conflict in the lecture schedule. Lecturers who teach courses, students cannot take certain courses because the lecture schedule they are taking conflicts with other lecture schedules. The main problem in this research is the design of lecture schedules which always conflict due to room availability and lecturer teaching hours. As a result, lecture scheduling becomes more complicated. The case study used is the scheduling of lectures for the Mathematics Department, Faculty of Science and Technology, UIN Sumatera Utara, Medan in the even semester of the 2022/2023 academic year. In this research, a bipartition graph will be formed based on the variables used, namely determining the variable index used in the course, teaching lecturer, teaching time, entry time, exit time, classroom, number of credits, semester and color. After that, the Welch Powell Algorithm will be used to solve the scheduling problem of a bipartition graph which is formed by creating nodes, membership matrix and the final result is a tabulation of the colored bipartition graph as the output of the scheduling. This algorithm also uses MATLAB software. From the results obtained, the algorithm provides an effective digital solution in designing lecture roster scheduling which is still done manually. This will help the mathematics department in overcoming the problems mentioned above. The research results will be explained detail in the results and discussion section.